Misdiagnosis and Chemotherapy Delaying Reduces the Chemosensitivity of Choriocarcinoma Patient: Analysis of 36 Cases - Lin-Jing Yuan; Yu-Ying Chen; Cai-Xia Zhu; Yi-Zi Wang; Guo-Fen Yang (IMR Press, 2022)
Background: Choriocarcinoma is a curable malignant neoplasm when chemotherapy is properly implemented. However, when chemotherapy resistance occurs, disease can be fatal. Misdiagnosis is common, which may lead to delaying of the first cycle of chemotherapy and increase the possibility of chemoresistance. Methods: We analyzed 36 choriocarcinoma cases who were treated in our department about their clinical characteristics, and their diagnosis and treatment processes together with the serum β-hCG variation. Results: Analysis showed that the disease onset age, FIGO (International Federation of Gynecology and Obstetrics) stage distribution were similar to the other cohort. The primary origins were uterine canals, and the serum β-hCG elevated with or without vaginal bleeding were common, which all easily lead to misdiagnosis of benign pregnancy related diseases. Our data demonstrated that the misdiagnosis of choriocarcinoma resulted in delaying of the first cycle of chemotherapy, followed by decreased control of serum β-hCG after one chemotherapy cycle and more cycles for serum β-hCG normalization, which meant the possibility of generating chemoresistance. Conclusions: In summary, standardized surveillance and treatment process to decrease misdiagnosis rate of choriocarcinoma can be an effective measure to improve the prognosis of patients.